(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article brings considerations about the scene as an expanded field from the notion of environment present in proposals and projects by Richard Schechner and Hélio Oiticica and from the perspectives of the Viewpoints practice. It is proposed heir a look at the opening of the scene, taking into account initiatives that articulate body, space and time in the creation processes. Schechner and Oiticica create environmental proposals that expand the possibilities for thinking on the phenomenon of art as a space of relationship in time and space. The Viewpoints, in its turn, encourages the investigation of this environmental field from the point of view of the scene’s practice and experience. It is intended, therefore, to approach perspectives of an enlarged scene taking into account the notion of environment, as well as the environmental experiences proposed by Viewpoints.